2009
DOI: 10.1126/science.1175865
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd6 Catalyses Lysyl-Hydroxylation of U2AF65, a Protein Associated with RNA Splicing

Abstract: 10. These authors contributed equally to the work.11. These authors contributed equally to the work. AbstractThe metazoan hypoxic response is regulated by the oxygen-dependent posttranslational hydroxylation of the -subunits of the hypoxia inducible factor (HIF)system. This identification has raised the question of whether other proteinhydroxylases are involved in the regulation of gene expression. Here we demonstrate that the splicing factor protein U2AF65 undergoes post-translational lysyl-5-hydroxylation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
421
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(445 citation statements)
references
References 28 publications
17
421
6
1
Order By: Relevance
“…The hydroxylation reaction of Jmjd6 critically depends on the oxygen concentration; hence Jmjd6 is expected to be inhibited under conditions of severe hypoxia (19). Therefore, we investigated the effect of hypoxia on sFlt1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydroxylation reaction of Jmjd6 critically depends on the oxygen concentration; hence Jmjd6 is expected to be inhibited under conditions of severe hypoxia (19). Therefore, we investigated the effect of hypoxia on sFlt1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Jmjd6 was recently reported to hydroxylate the splicing factor U2AF65 (19). Therefore, we investigated whether U2AF65 might mediate Flt1 splicing and bind to Flt1 mRNA.…”
Section: Recovery Of the Inhibited Angiogenic Phenotype After Jmjd6 Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahman et al have demonstrated that the conserved extraterminal domain of all three BET proteins, BRD2, BRD3, and BRD4, associates with several chromatin-modifying factors (29), which include the H3K36 methyltransferase NSD3 (30); ATAD5, a replication factor involved in the ATM/ATR-mediated DNA damage response (31,32); CHD4, a component of the transcriptional repressor mi-2/NURD complex that mediates nucleosome repositioning (33); and JMDJ6, originally reported to be a histone arginine demethylase but more recently implicated in lysyl hydroxylation of splicing factor U2AF65 (34,35). Further studies are needed to determine the roles of these chromatin modulators in T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenase catalyzes hydroxylation of ribosomal proteins which regulate gene transcriptions (13). It is suggested that oxygenases also catalyze demethylation of N-ε-methyllysine histone residues (JmjC demethylases) (14) and lysyl 5-hydroxylation of splicing-related proteins (JMJD6) (15). Mdig/mina53 interacts with various ribosomal proteins and is involved in ribosome biogenesis (6) and ribosomal RNA transcription (12).…”
Section: Hydroxylation Of Ribosomal Proteinmentioning
confidence: 99%